A rare case of fondaparinux-induced major bleeding in postmenopausal woman prescribed for non-ST segment elevation Ml - Tandon, Vishal R. (Medknow Publications & Media Pvt Ltd, 2013)
Fondaparinux sodium is a synthetic, sulfated pentasaccharide, selective factor Xa inhibitor, a safe and effective antithrombotic agent indicated for preventing thrombus formation in patients with acute coronary syndromes, including those with ST-segment elevation myocardial infarction (STEMI), non-STEMI (NSTEMI), or unstable angina. Major bleeding is rarely known to exist with the use of fondaparinux and to best of our knowledge there exist no isolated case report presenting with fondaparinux-induced major bleeding prescribed for recently diagnosed NSTEMI. The case report highlights, a need for clinicians to have a sound understanding of anticoagulant pharmacology, dosing, toxicity, individualized approach, and predicting the risk of bleeding before they are prescribed to advancing age persons.